Clinical Features and Risk Factors of Active Tuberculosis in Patients with Behçet’s Disease - Yaxu Liu; Lifan Zhang; Ziyue Zhou; Luxi Sun; Baotong Zhou; Xiaoqing Liu; Wenjie Zheng (Journal of Immunology Research)
To investigate the clinical features and potential risk factors of active tuberculosis (ATB) in Behçet’s disease (BD), we conducted a case-control study on hospitalized BD patients in our institute from 2010 to 2019. BD patients with ATB were enrolled as the case group. The control group was selected by random number sampling from the remaining BD patients, including those with latent tuberculosis infection, previous tuberculosis, or without tuberculosis. Finally, we reviewed 386 BD patients and identified 21 (5.4%) ATB cases, including four (19.0%) microbiologically confirmed and 17 (81.0%) clinically diagnosed. We found that BD patients with ATB were more prone to have systemic symptoms (fever, night sweating, and unexplained weight loss) and/or symptoms related to the infection site. Multivariate logistic regression analysis revealed that erythrocyte sedimentation rate ESR>60 mm/h (OR=13.710, 95% CI (1.101, 170.702)), increased IgG (OR=1.226, 95% CI (1.001, 1.502)), and positive T-SPOT.TB (OR=7.793, 95% CI (1.312, 48.464), for 24-200 SFC/106PBMC; OR=17.705 95% CI (2.503, 125.260), for >200 SFC/106PBMC) were potential risk factors for ATB in BD patients. Our study suggested that when BD patients have systemic symptoms with significantly elevated TB-SPOT, the diagnosis of ATB should be considered.